2019
DOI: 10.3892/mmr.2019.10238
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics analysis of sirolimus treatment in lupus nephritis

Abstract: lupus nephritis (ln) is one of the principal causes of mortality and disability in patients with systemic lupus erythematosus. Sirolimus has been used to treat patients with ln; however, the effects and mechanism of sirolimus in these patients remains unclear. The present study aimed to elucidate the therapeutic effects and mechanisms of sirolimus in ln mice using low, medium and high doses of sirolimus (0.1, 0.3 and 1 mg/kg, respectively). The survival probability and kidney index were calculated, and renal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In addition, it has previously been reported that the epithetlial-mesenchymal transition (EMT) is significantly correlated with renal fibrosis, which is associated with calcineurin inhibitor-mediated nephrotoxicity (21). EMT is one of the basic mechanisms of renal fibrosis and involves various processes in which epithelial cells stop exhibiting epithelial characteristics, including the expression of E-cadherin, and obtain traits specific of mesenchymal cells, including the upregulation of α-SMA (25,47-48). In addition, it has previously been reported that vimentin is a potential novel biomarker in renal fibrosis (25,49).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, it has previously been reported that the epithetlial-mesenchymal transition (EMT) is significantly correlated with renal fibrosis, which is associated with calcineurin inhibitor-mediated nephrotoxicity (21). EMT is one of the basic mechanisms of renal fibrosis and involves various processes in which epithelial cells stop exhibiting epithelial characteristics, including the expression of E-cadherin, and obtain traits specific of mesenchymal cells, including the upregulation of α-SMA (25,47-48). In addition, it has previously been reported that vimentin is a potential novel biomarker in renal fibrosis (25,49).…”
Section: Discussionmentioning
confidence: 99%
“…After Wistar rats were sacrificed, the kidneys were removed and weighed. The kidney index was calculated using the following formula: Kidney index = (average kidney weight/body weight) (25). Paraformaldehyde (4%) was used to fix the fresh kidneys, and liquid nitrogen was used to rapidly freeze the residual kidney tissues, which were stored at -80°C until further analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations